A scalable synthesis of N-doped Si nanoparticles for high-performance Li-ion batteries. Issue 19 (11th February 2016) - Han, Ying; Lin, Ning; Qian, Yuying; Zhou, Jianbin; Tian, Jie; Zhu, Yongchun; Qian, Yitai
Abstract : N-doped Si nanoparticles were prepared synchronously using a nitridation process of Mg2 Si, which exhibited excellent electrochemical performance for lithium ion batteries. Abstract : N-doped Si nanoparticles were prepared synchronously by nitridation of Mg2 Si. The existence of nitrogen doping can be demonstrated by the XPS spectrum and EELS energy-filtered images. When the N-doped Si nanoparticles were used as an anode for Li-ion batteries, a high reversible capacity of 2595 mA h g −1 at 0.36 A g −1 after 40 cycles, and 805 mA h g −1 at 3.6 A g −1 after 800 cycles could be obtained.